2018
DOI: 10.1530/rep-18-0112
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase suppresses the cytotoxicity of 1 NK cells in response to ectopic endometrial stromal cells in endometriosis

Abstract: It has been reported that the impaired cytotoxicity of natural killer (NK) cells and abnormal cytokines that are changed by the interaction between ectopic endometrial cells and immune cells is indispensable for the initiation and development of endometriosis (EMS). However, the mechanism of NK cells dysfunction in EMS remains largely unclear. Here, we found that NK cells in peritoneal fluid from women with EMS highly expressed indoleamine 2,3-dioxygenase (IDO). Furthermore, IDO+NK cells possessed lower NKp46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Currently, the cause of reduced immunosurveillance of endometriotic lesions in the pelvic cavity of women with endometriosis is unknown. One of the components of this reduced immunosurveillance is the inhibition of NK cells (Oosterlynck et al, 1991;Oosterlynck et al, 1992;Liu et al, 2018;Xu, 2019). Therefore, in the present study, we investigated if ESC cyst may also be involved in NK cell-mediated inhibition, because we previously found that they may possess immunosuppressive properties (Abomaray et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Currently, the cause of reduced immunosurveillance of endometriotic lesions in the pelvic cavity of women with endometriosis is unknown. One of the components of this reduced immunosurveillance is the inhibition of NK cells (Oosterlynck et al, 1991;Oosterlynck et al, 1992;Liu et al, 2018;Xu, 2019). Therefore, in the present study, we investigated if ESC cyst may also be involved in NK cell-mediated inhibition, because we previously found that they may possess immunosuppressive properties (Abomaray et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…However, it seems that the effects on the NK cells are mostly mediated through macrophages and not ESC cyst , since NK cell cytotoxicity was not reduced following coculture with only ESC cyst (Yang et al, 2017). In another study, NK cells were cultured with ESC endohv or ectopic ESC; it was found that the NK cells significantly enhanced their expression of the immunosuppressive enzyme indoleamine 2,3-dioxygenase (IDO), especially following culture with ectopic ESC, and the effect was partly due to ESC-derived TGFβ1 (Liu et al, 2018). Moreover, when the NK cells were in turn cultured with ectopic ESC, their cytotoxicity was significantly inhibited, and this was attributed to their expression of IDO (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important observation indicating that the cultured cells retain malignant phenotype with high IDO1 [ 24 , 44 ] and HER2 expression observed in vivo [ 59 ]. Together, it makes this model suitable for identification and testing novel immunotherapeutics for HER2- and IDO1-associated pathology shown to be important in endometrial cancer [ 45 ] or endometriosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the kynurenine pathway (KP), responsible for the generation of several toxic metabolites called kynurenines, modulates local immune tolerance [ 20 , 21 ]. IDO1 activity is of great interest for scientists studying biology and pathology of endometrium [ 22 ]. Recently, KP has been also recognized as a novel factor in endometrial cancer tissue [ 23 ].…”
Section: Introductionmentioning
confidence: 99%